A theoretical and experimental model of flow characteristics in subretinal injections - Reza Ladha; Benjamin Merveille; Roland Wyns; Benoit Scheid; François Willermain; Marc D. de Smet (PLoS ONE, 2026)
Subretinal injections (SI) are used to deliver gene therapies for inherited retinal diseases, yet the optimal injection parameters remain undefined. This study used theoretical and experimental models to quantify the relationship between injection pressure, flow dynamics, and residual flow. A theoretical model (TM) was developed based on the Hagen-Poiseuille law and the theory of a jet immersed in the same liquid. An experimental model (EM) was constructed to allow for measuring flow and residual flow across injection pressures ranging from 0 to 20 psi. We assessed the effects of ambient pressure, injection system tubing length, and syringe priming technique. A minimum pressure of 6 psi was required to generate a detectable flow in the EM. Jet speed increased with the square root of injection pressure, aligning with theoretical predictions. Residual flow persisted for 28–47 seconds after injection and increased logarithmically with injection pressure. Elevated ambient pressure (45 mmHg) only reduced flow at lower injection pressures. The “lock-and-load” priming method decreased jet speed and increased residual flow compared to the “load-and-lock” method. Both TM and EM quantified SI flow dynamics, with EM demonstrating residual flow at all tested pressures. To minimize complications, clinicians should use the lowest injection pressure and allow sufficient time for the cannula to be withdrawn from the subretinal space.